Soluble Fms-Like Tyrosine Kinase-1 Alters Cellular Metabolism and Mitochondrial Bioenergetics in Preeclampsia - Sánchez-Aranguren, Lissette C.; Espinosa-González, Cindy T.; González-Ortiz, Laura M.; Sanabria-Barrera, Sandra M.; Riaño-Medina, Carlos E.; Nuñez, Andrés F.; Ahmed, Asif; Vasquez-Vivar, Jeannette; López, Marcos (Frontiers in Physiology, 2018)
Preeclampsia is a maternal hypertensive disorder that affects up to 1 out of 12 pregnancies worldwide. It is characterized by proteinuria, endothelial dysfunction, and elevated levels of the circulating form of the vascular endothelial growth factor receptor-1 (VEGFR-1, known as sFlt-1). sFlt-1 effects are mediated in part by decreasing VEGF signaling. The direct effects of sFlt-1 on cellular metabolism, and bioenergetics in preeclampsia, have not been established. The goal of this study was to evaluate whether sFTL-1 causes mitochondrial dysfunction leading to disruption of normal functioning in endothelial and placental cells in preeclampsia. Endothelial cells (ECs) and first-trimester trophoblast (HTR-8/SVneo) were treated with serum from preeclamptic women rich in sFtl or with the recombinant protein. sFlt-1, dose-dependently inhibited ECs respiration and acidification rates indicating ametabolic phenotype switch enhancing glycolytic flux. HTR-8/SVneo displayed a strong basal glycolytic metabolism, remaining less sensitive to sFlt-1-induced mitochondrial impairment. Moreover, ECs exposed to serum from preeclamptic subjects demonstrated that increased sFtl1 leads to metabolic perturbations accountable for mitochondrial dysfunction observed in preeclampsia. sFlt-1 exacerbated mitochondrial reactive oxygen species (ROS) formation and mitochondrial membrane potential dissipation in ECs and trophoblasts exposed to serum from preeclamptic women. Forcing oxidative metabolism by culturing cells in galactose media, further sensitized cells to sFlt-1. This approach let us establish that sFlt-1 targets mitochondrial function in ECs. The effects of sFlt-1 on HTR-8/SVneo cells metabolism was amplified in galactose, demonstrating that sFlt-1 will only target cells that rely mainly on oxidative metabolism.. Together these findings indicate sFTl1 mediates of oxidative stress and loss of function predominantly in ECs, which maybe a significant event in sFtl1 preeclampsia mechanisms.